CHINESE STRATEGY TOWARD CENTRAL AND SOUTH ASIA: ENERGY INTERESTS AND ENERGY SECURITY - N. Marketos, Thrassyvoulos (CENTRAL ASIA AND THE CAUCASUS, 2012)
As China’s economy has grown and become integrated into the global market, both have become interdependent. Therefore China’s long-term development goals will only be possible with increasing and stable access to foreign trade, resources, and energy. The latter has become a pressing issue as the country’s dependence on international energy imports rapidly increases and might impose a limit on its growth if left unmet. This is especially important given supply shortages as a result of the recent events in Libya and given the future prospect of supply disruptions from the Middle East. In the case of oil, the International Energy Agency (IEA) forecast in 2010 that Chinese imports would grow from 4.3 million barrels a day (m/bd) in 2009 to 12.8 m/bd in 2035, thus rising from 53% to 84% of the total demand. The issue of resource shortages will play an even more prominent role in international relations and will become an increasing source of conflict among major powers. Given the fact that some countries are more generously endowed with strategic resources, this opens up the possibility of using these tools for political gain. Historically, economic diplomacy has contributed to the shifting balance of power in the world. Nations have more often been inclined to employ economic measures in pursuit of foreign policy objectives when “the legitimacy of the power of existing structures of international cooperation decreases.” The result of the current realignment of geo-economic power will encourage nations to reassess the effectiveness of their energy, economic, and foreign policies. In 2011, the U.S. Department of Defense Annual Report indicated that Beijing’s regional energy strategy is geared to alleviate China’s heavy dependence on sea lines of communication (SLOC) and in particular on the South China Sea and the Straits of Malacca and Hormuz. At present, it has a limited ability to control the flow of commodities over the Indian Ocean and through these straits. In response, China has invested heavily in bilateral relations and in developing infrastructure to support its fleet in Pakistan, Bangladesh, Sri Lanka, and Myanmar. Also China has multiple agreements to pipe oil and natural gas in from energy-rich Central Asian neighbors. The country is constructing a pipeline through Myanmar to bypass the Strait of Malacca. In spite of these developments, new land pipelines will only slightly alleviate the growing need in the future for maritime-based hydrocarbon transport. Also Central Asian oil can be too much of a good thing. On any given day, Russia is the world’s first or second largest oil producer, second largest oil exporter, and second largest gas producer. As Anatol Lieven says, Russia has long assumed China would be forced to depend on it for………